Urinary Tract Infections in a Neonatal Intensive Care Unit - Weems, Mark F.; Wei, Daniel; Ramanathan, Rangasamy; Barton, Lorayne; Vachon, Linda; Sardesai, Smeeta (American Journal of Perinatology, 2015)
Objective Our aim was to describe laboratory findings and imaging results for neonatal patients diagnosed with urinary tract infection (UTI).Study Design Medical records were reviewed for infants diagnosed with UTI in a single neonatal intensive care unit (NICU) over a 13-year period.Results Of the 8,241 patients admitted to the NICU during the study period, 137 infants were diagnosed with UTI. Imaging was reviewed for 101 patients. Renal pelvis dilation was found in 34% of patients and vesicoureteral reflux was found in 21%. Renal pelvis dilation was not associated with reflux (OR: 0.53 [95% CI: 0.18–1.5]). The sensitivity of urinalysis to detect a positive culture was 76%, and the specificity was 41%. Tests of cure for bacterial infections were uniformly negative.Conclusion Renal pelvis dilation was common but not associated with reflux among NICU patients diagnosed with UTI. Diagnostic criteria in this population are not well defined, and guidelines are needed for diagnosis and management of UTIs in NICU patients.
Keywords: ultrasound; voiding cystourethrogram; vesicoureteral reflux; neonate; infant; urinary tract infection